2017
DOI: 10.1093/jpids/piw068
|View full text |Cite
|
Sign up to set email alerts
|

Time to Change Dosing of Inactivated Quadrivalent Influenza Vaccine in Young Children: Evidence From a Phase III, Randomized, Controlled Trial

Abstract: Background.Children under 3 years of age may benefit from a double-dose of inactivated quadrivalent influenza vaccine (IIV4) instead of the standard-dose.Methods.We compared the only United States-licensed standard-dose IIV4 (0.25 mL, 7.5 µg hemagglutinin per influenza strain) versus double-dose IIV4 manufactured by a different process (0.5 mL, 15 µg per strain) in a phase III, randomized, observer-blind trial in children 6–35 months of age (NCT02242643). The primary objective was to demonstrate immunogenic no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
(30 reference statements)
2
25
1
Order By: Relevance
“…In a randomized trial comparing immunogenicity and safety of 0.5 mL FluLaval Quadrivalent with 0.25 mL Fluzone Quadrivalent, safety and reactogenicity were similar between the two vaccines. In a post-hoc analysis, superior immunogenicity was noted for the B components of FluLaval Quadrivalent among infants aged 6 through 17 months and for unprimed children (those who had not previously received at least 2 doses of influenza vaccine) aged 6 through 35 months ( 30 ).…”
Section: Recommendations For the Use Of Influenza Vaccines 2017–18 Smentioning
confidence: 99%
“…In a randomized trial comparing immunogenicity and safety of 0.5 mL FluLaval Quadrivalent with 0.25 mL Fluzone Quadrivalent, safety and reactogenicity were similar between the two vaccines. In a post-hoc analysis, superior immunogenicity was noted for the B components of FluLaval Quadrivalent among infants aged 6 through 17 months and for unprimed children (those who had not previously received at least 2 doses of influenza vaccine) aged 6 through 35 months ( 30 ).…”
Section: Recommendations For the Use Of Influenza Vaccines 2017–18 Smentioning
confidence: 99%
“…24 A post hoc analysis showed superior immunogenicity for the B strain components of FluLaval Quadrivalent among children aged 6 through 17 months and those who had not previously received at least two doses of influenza vaccine. 24 The authors concluded that the double dose may improve protection against influenza B in some young children.…”
Section: With Influenza Activity In the Community Increasing It Is Dmentioning
confidence: 98%
“…23 FluLaval demonstrated safety and efficacy of the double dose for children younger than age 3 in a Phase III, randomized, observer-blinded, controlled trial. 24 The study assessed immunogenicity (geometric mean titers and seroconversion rate) in the per-protocol cohort (n = 2,041) and safety (adverse event reports) in the intent-to-treat cohort (n = 2,424). 24 Safety and reactogenicity were similar for a 0.5-mL dose of FluLaval Quadrivalent and a 0.25-mL dose of Fluzone Quadrivalent.…”
Section: With Influenza Activity In the Community Increasing It Is Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized trial comparing immunogenicity and safety of 0.5 mL FluLaval Quadrivalent with 0.25 mL Fluzone Quadrivalent, safety and reactogenicity were similar between the two vaccines. In a post‐hoc analysis, superior immunogenicity was noted for the B components of FluLaval Quadrivalent among infants aged 6 through 17 months and for unprimed children (those who had not previously received at least 2 doses of influenza vaccine) aged 6 through 35 months .…”
Section: Recommendations For the Use Of Influenza Vaccines 2017–18 Smentioning
confidence: 98%